The interplay between HPV, other Sexually Transmissible Infections and genital microbiome on cervical microenvironment (MicroCervixHPV study) - Gonçalves-Nobre, J. Guilherme; Matos, Andreia; Carreira, Mariana; Santos, Ana Carolina; Veiga, Luisa Carvalho; Ginete, Catarina; Brito, Miguel; Pires, Marina; Pereira, Hermínia; Cardoso, Carlos; Bicho, Manuel; Bicho, Maria Clara (Frontiers in Cellular and Infection Microbiology, 2024)
The importance of Cervicovaginal Microbiota in protecting against infections (such as HPV) is already well established, namely through Lactobacillus spp., as well as the mechanism through which HPV leads to Cervical Neoplasia. However, it is not possible to classify HPV as a complete carcinogen. Thus, the importance of exploring Cervicovaginal dysbiosis with the intention of deciphering this interaction with HPV, takes on greater relevance. The main objectives of this study were: 1) Comparison of the MCV composition of women with or without HPV and women with ASCUS or LSIL; 2) Characterization of cytokines present in the vaginal microenvironment; 3) Evaluation of the blood count ratios as prognostic systemic inflammatory biomarkers; 4) Correlation between MCV, HPV serotypes and cytokines.Methods: This was a retrospective, observational, multicenter, cross-sectional study. CVM analysis was performed by isolation RNA and sequencing on a NGS platform. Cytokine concentrations of CVM were obtained through Multiplex platform. Statistical analysis was performed in SPSS v 26.0. An α of 0.05 was considered statistically significant.Highlighting the core of the study, CVM types of CST I and CST IV were found to influence the emergence of cervical lesions. Neutrophil-to-Lymphocyte ratio was found to impact the prognosis of ASCUS. Within CVM, Lactobacillus prevent the growth of other CST IV species, while the latter express symbiotic relationships with each other and show affinity for specific HPV serotypes. At last, RANTES chemokine is significantly elevated in cervicovaginal infections.The importance of using vaginal cytokine profiles and CVM is highlighted in the hypothesis of prevention of Cervical Neoplasia development, as well as in its use as a prognostic biomarker. Taken together, these insights are one step closer to personalized medicine.